Astaxanthin in cardiovascular health and disease: mechanisms of action, therapeutic merits, and knowledge gaps. Issue 1 (7th December 2016) - Visioli, Francesco; Artaria, Christian
Abstract : Cardiovascular disease is the main contributor to morbidity and mortality worldwide. Abstract : Cardiovascular disease is the main contributor to morbidity and mortality worldwide. Based on its unique chemical features, the xanthophyll carotenoid astaxanthin is being proposed as a suitable preventive and therapeutic agent in cardiovascular disease. This review focuses on recent advances in astaxanthin research relevant to cardiovascular health and disease, i.e. its direct antioxidant, indirect antioxidant, anti-inflammatory, anti-hypertensive, anti-diabetic, renoprotective, lipid-lowering and anti-atherosclerotic activities in vitro and in vivo . Disparities in the biological activities and health benefits of astaxanthin observed in vitro (strong evidence), in animals (moderate evidence), and in humans (weak evidence) and the variety of astaxanthin sources hamper efforts to establish areas of astaxanthin application in human health care. A list of knowledge gaps and experimental pitfalls is proposed to overcome some of the short-comings in astaxanthin research.